Laws of the constitution : consolidated - Bur, D. F. (Donald F.); Canada (Edmonton : University of Alberta Press, 2021)
"Laws of the Constitution: Consolidated gathers all of the historical and contemporary constitutional documents pertaining to Canada, its provinces, and its territories, organized thematically and topically for ease of reference and supported by comprehensive lists and a thorough index. The volume excludes overridden and irrelevant documents, making it a comprehensive yet focused and precise reference that presents the words, ideas, and documents that have brought the constitution into being. A must for academic libraries, Bur's compilation is an indispensable resource for lawyers and scholars in Canadian constitutional law, as well as historians, political scientists, policy makers, and anyone interested in constitution-making."--
General principles -- Acquisition of territory -- Creation of government -- Acquisition of property -- Union, transition to union and conditions of union -- Distribution of powers -- Executive authority -- Parliamentary structures and procedures -- Distribution of property -- Territories, parliamentary structures and procedures -- Protection of rights -- Aboriginal rights -- Boundaries -- Amendment of the constitutions.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 27, 2025).
eBooks on EBSCOhost
Keywords: Canada; Constitution Act, 1982 (Canada); Constitutions -- Canada; Constitutional history -- Canada; Constitutions -- Canada; Histoire constitutionnelle -- Canada; Constitutional history; Constitutions; Canada; Canada; Constitutional history; Constitutions